THE IMPACT OF GENDER INEQUALITY ON ECONOMIC GROWTH AND HUMAN DEVELOPMENT IN INDONESIA - Hermaniar, Irma; Hidayati, Firda; Yumarni, Tri (Faculty of Administrative Science, Universitas Brawijaya, 2025)
Indonesia has maintained steady economic growth and human development over the past decade, yet gender inequality persists. This study examines how gender inequality affects both economic growth and human development in Indonesia, addressing a literature gap by analyzing both simultaneously. Using nine years of panel data at provincial and national levels, we combine descriptive analysis with Feasible Generalized Least Squares (FGLS) panel regressions. Key indicators are the Gross Regional Domestic Product (GRDP) growth rate, Human Development Index (HDI), and Gender Inequality Index (GII). Results show a significant negative effect of GII on both GRDP growth and HDI. Regional disparities highlight the roles of culture and infrastructure, with Eastern Indonesia facing greater inequality. Policy priorities include strengthening maternal and adolescent health services, expanding girls’ access to quality education, increasing women’s political representation, and removing labor-market barriers to accelerate economic growth and human development